Health entrepreneurship : a guide - Rich, Carrie R.; Singleton, Knox; Vernooij, Mark; Wadhwa, Seema S. (Routledge, 2019)
The potential for health professionals to learn and practice the process of entrepreneurship to improve the quality of health care and services is enormous and untapped. Health professionals witness first-hand where changes to the health system should be made and where opportunities for improvement arise, yet they are seldom associated with entrepreneurship. Incorporating the authors' experiences leading health systems, working on the front line and supporting corporations, NGOs and accelerators that target health entrepreneurship, this book explores: The why, what and how of entrepreneurship - and intrapreneurship - for health professionals. Resources to encourage innovation by guiding the reader through an idea development process specific to the experience and working environment of health professionals. The areas of need, developing ideas and prototype solutions, as well as implementing, scaling and pitching entrepreneurial ideas. An accessible and applied guide, Health Entrepreneurship introduces ideas about the practical delivery and implementation of entrepreneurial ideas, allowing readers to affect necessary and positive change.